New Perspectives on Low-Fidelity Prototyping: A Systematic Mapping Study on Tools and Functionalities - Resende da Silva Scapim, Gabriel; Camila Lapasini Leal, Gislaine; Corredato Guerino, Guilherme (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2025: Anais do XXIV Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais, 2025)
Introduction: Low-fdelity prototyping is a key approach in User-Centered Design (UCD), enabling quick and cost-effective exploration of interface ideas before implementation. Objective: Identify and characterize low-fidelity prototyping tools with respect to their functionalities, limitations, and applicability. Methodology: A Systematic Mapping Study (SMS) was conducted. From an initial sample of 1493 publications obtained on Scopus, IEEE Xplore, ACM Digital Library, and ScienceDirect, we selected 37 studies after applying inclusion and exclusion criteria. Results: We identified 22 low-fidelity prototyping tools, highlighting Figma, Balsamiq, and PowerPoint as the most frequently cited. Results show limited integration of emerging technologies such as artificial intelligence, reduced functionality in tools exclusively made for low-fidelity prototyping, and scarce incorporation of structured design guidelines, leaving quality assurance primarily as a software professional’s responsibility.